The Role of Gender in Digital Content Influences on Impulse Buying - Teguh Lingga Mukti; Sudarmiatin Sudarmiatin; Titis Shinta Dhewi (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study examines how user generated content and live streaming influence impulse buying behavior in a digital marketing environment, with electronic word of mouth and gender as explanatory mechanisms being tested. Focusing on consumers of Mykonos perfume on the Shopee platform, this study uses a quantitative approach with 385 respondents and analyzes structural relationships using PLS-SEM. The results show that live streaming is the most powerful digital stimulus because it can directly increase impulse buying while encouraging consumers to generate online reviews and comments. Conversely, user-generated content does not directly affect impulse buying but becomes effective when it triggers electronic word of mouth, thus demonstrating a full mediating effect. Electronic word of mouth itself has a significant effect in encouraging impulsive purchases by increasing consumer confidence and emotional responses. Gender was also found to moderate the relationship between variables, with men being more easily influenced by live streaming, while women were more responsive to reviews and digital social interactions. These findings confirm that real-time stimuli, user-to-user communication, and demographic characteristics work simultaneously in shaping spontaneous purchasing decisions in the e-commerce environment.